Topik Perkara Pelanggaran Pasal 27 UU ITE di Wilayah Hukum Nusa Tenggara Timur: Analisis Wacana Kritis (Topics of Violations of Article 27 of the ITE Law in the East Nusa Tenggara Legal Territory: Critical Discourse Analysis) - Salimulloh Tegar Sanubarianto; Winci Firdaus (Indonesian Language Education and Literature, 2022)
This study aims to describe the topic of cases of violations of Article 27 of the ITE Law in the jurisdiction of East Nusa Tenggara through the corpus with the help of AntConc software. The results of the study show personal pronouns of the second-person singular and greeting words such as kau, kamu, saudara, lu, anjing, lelak, puki, nona, pukimai, babi, pelacur, mai, wanita, lonte, betina, situ, tolo, perempuan, ular, lasu, Yang Mulia, nyong, anak, dan laknat, predominately appear in the corpus. The second-person singular personal pronouns and greeting words that appear are mostly associated with women. The results of the collocation and concordance analysis show that the topic of infidelity is the main and very dominant topic, followed by the topic of inheritance rights and conflict at work. It is necessary to conduct research with a much larger corpus of data so that potential conflicts in the digital world can be mapped and mitigated.Penelitian ini bertujuan mendeskripsikan topik perkara pelanggaran Pasal 27 UU ITE di wilayah hukum Nusa Tenggara Timur melalui korpus dengan bantuan peranti lunak AntConc. Hasil dari penelitian menunjukkan pronomina persona orang kedua tunggal dan kata sapaan seperti kau, kamu, saudara, lu, anjing, lelak, puki, nona, pukimai, babi, pelacur, mai, wanita, lonte, betina, situ, tolo, perempuan, ular, lasu, Yang Mulia, nyong, anak, dan laknat, secara dominan muncul dalam korpus. Pronomina persona orang kedua tunggal dan kata sapaan yang muncul pun kebanyakan berasosiasi dengan perempuan. Hasil analisis kolokasi dan konkordansi menunjukkan bahwa topik perselingkuhan menjadi topik utama dan sangat dominan, disusul topik hak waris, dan konflik dalam pekerjaan. Perlu dilakukan penelitian dengan data korpus yang jauh lebih besar sehingga potensi konflik di dunia digital dapat dipetakan dan diredam.